An analysis into the effects of downsizing as a measure of cost containment on company performance - Mhike, Jotam (Midlands State University, 2017)
The aim of this research was to make an analysis into the effects of downsizing as a measure of cost containment on company performance and to make relevant suggestions to mitigate the shortfalls. Forty-two questionnaires and five interviews were used as data collection instruments necessary for collection of data. Primary and secondary sources were both used to obtain data. The use of literature as well as findings obtained from data collected revealed that downsizing in most cases is initiated as a result of shareholders demand for higher returns and the need to maintain competitive advantage of the company. It highlighted on the effects of downsizing to company performance, victims and survivors of downsizing. It also explained the risks that are likely to be encountered when carrying out the policy. The use of tables, pie charts and graphs were used to display data after analysis. The data and information obtained indicated that downsizing if not carried out properly the benefits associated are of short-term nature. This dissertation looked at some of the principles that need to be adopted when downsizing. It also examined the importance of costing techniques that can be implemented other than downsizing to improve company performance. The major recommendations are that; management must adopt responsibility accounting and clearly define lines of authority and set budgets for every department or division as a measure of performance, human resources department must be involved in the implementation of the policy to mitigate risks associated with downsizing and there should be retrenchment training for the victims of downsizing so that the pressure and stress can be eased.